Review article: emerging insights into the immunopathology, clinical and therapeutic aspects of hepatitis delta virus - Usai, Carla; Gill, Upkar S.; Riddell, Anna C.; Asselah, Tarik; Kennedy, Patrick T. (Alimentary pharmacology & therapeutics, 2022)
Summary Background Hepatitis delta virus (HDV), which causes the most severe form of viral hepatitis, is an obligated hepatitis B (HBV) satellite virus that can either infect naïve subjects simultaneously with HBV (co‐infection), or chronically infect HBV carriers (super‐infection). An estimated 12 million people are infected by HDV worldwide. Aims To summarise the most relevant aspects of the molecular biology of HDV, and to discuss the latest understanding of the induced pathology, interactions with the immune system, as well as both approved and investigational treatment options. Methods References for this review were identified through searches of PubMed with the terms “HDV” “viral hepatitis” “co‐infection” and “super‐infection,” published between 1980 and October 2021 Results The limited access to the HDV‐infected liver has hampered the investigation of the intrahepatic compartment and our understanding of the mechanisms of HDV pathogenesis. In the absence of standardised and sensitive diagnostic tools, HDV is often underdiagnosed and owing to its strong dependence on host cellular factors, the development of direct antiviral agents has been challenging. New therapeutic agents targeting different steps of the viral cycle have recently been investigated, among which bulevirtide (which was conditionally approved by EMA in July 2020) and lonafarnib; both drugs having received orphan drug designation from both the EMA and FDA. Conclusions The HBV cure programme potentially offers a unique opportunity to enhance HDV treatment strategies. In addition, a more comprehensive analysis of the intrahepatic compartment is mandated to better understand any liver‐confined interaction of HDV with the host immune system. The diagrams show the time‐course of the most common outcomes of (A) HBV‐HDV co‐infection and (B) HDV super‐infection of an HBV carrier. Biochemical and serological parameters are indicated.